Анализ вероятных путей утечки информации в банковских системах - Сягаева, О. А. (ХНУРЭ, 2012)
This work is devoted to the analysis of information leakage paths in the banking system. It was revealed that the most dangerous is the compromising emanations, formed channels electromagnetic radiation. Proposed development of a mathematical model of the source of a dangerous signal to protect the information
Keywords: утечка информации; банковская система